Phage display as a tool for identifying HIV-1 broadly neutralizing antibodies - A. N. Chikaev; A. P. Rudometov; Yu. A. Merkulyeva; L. I. Karpenko (Вавиловский журнал генетики и селекции, 2021)
Combinatorial biology methods offer a good solution for targeting interactions of specific molecules by a high-throughput screening and are widely used for drug development, diagnostics, identification of novel monoclonal antibodies, search for linear peptide mimetics of discontinuous epitopes for the development of immunogens or vaccine components. Among all currently available techniques, phage display remains one of the most popular approaches. Despite being a fairly old method, phage display is still widely used for studying protein-protein, peptide-protein and DNA-protein interactions due to its relative simplicity and versatility. Phage display allows highly representative libraries of peptides, proteins or their fragments to be created. Each phage particle in a library displays peptides or proteins fused to its coat protein and simultaneously carries the DNA sequence encoding the displayed peptide/protein in its genome. The biopanning procedure allows isolation of specific clones for almost any target, and due to the physical link between the genotype and the phenotype of recombinant phage particles it is possible to determine the structure of selected molecules. Phage display technology continues to play an important role in HIV research. A major obstacle to the development of an effective HIV vaccine is an extensive genetic and antigenic variability of the virus. According to recent data, in order to provide protection against HIV infection, the so-called broadly neutralizing antibodies that are cross-reactive against multiple viral strains of HIV must be induced, which makes the identification of such antibodies a key area of HIV vaccinology. In this review, we discuss the use of phage display as a tool for identification of HIV-specific antibodies with broad neutralizing activity. We provide an outline of phage display technology, briefly describe the design of antibody phage libraries and the affinity selection procedure, and discuss the biology of HIV-1-specific broadly neutralizing antibodies. Finally, we summarize the studies aimed at identification of broadly neutralizing antibodies using various types of phage libraries.